2007
DOI: 10.1029/2007gl030898
|View full text |Cite
|
Sign up to set email alerts
|

Compound effects of Antarctic sea ice on atmospheric pCO2 change during glacial–interglacial cycle

Abstract: The cause of low atmospheric CO2 concentrations during the Last Glacial Maximum (LGM) is important for understanding the role of the carbon cycle in climatic variation. We used an ocean general circulation model, coupled with a biogeochemical model, to examine the effect of sea‐ice expansion in the Southern Ocean on atmospheric CO2 concentration. We newly considered a possible additional effect of sea‐ice expansion in reducing biological activity as well as the effect of reduced gas‐exchange. We propose that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
39
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 14 publications
12
39
0
Order By: Relevance
“…The export fluxes of particulate organic matter of 10.5 and 10.4 GtC yr −1 in PIa and PIb ( Fig. 1e and f) are in line with observationally-based estimates of 5-20 GtC yr −1 (Jahnke and Jahnke, 2004;Falkowski et al, 1998;Laws et al, 2000;Louanchi and Najjar, 2000).…”
Section: Solubilitysupporting
confidence: 68%
See 1 more Smart Citation
“…The export fluxes of particulate organic matter of 10.5 and 10.4 GtC yr −1 in PIa and PIb ( Fig. 1e and f) are in line with observationally-based estimates of 5-20 GtC yr −1 (Jahnke and Jahnke, 2004;Falkowski et al, 1998;Laws et al, 2000;Louanchi and Najjar, 2000).…”
Section: Solubilitysupporting
confidence: 68%
“…The excess nitrate off the coast of Chile and in the Atlantic sector of the Southern Ocean is attributable to the deep-water supply via coastal upwelling or convective mixing. Our model does not consider temperature-dependent biological production (Oschlies and Garcon, 1999) or temperature-dependent remineralization (Laws et al, 2000). LGb Table 2.…”
Section: Validation Of Present Ocean Carbon Cycle Simulationmentioning
confidence: 99%
“…We found that light limitation of highly productive regions in both hemispheres caused by increased sea ice cover led to a global loss of 160 Pg C, equivalent to 8 ppm pCO 2 . Similar responses have been simulated in other models that consider the impact of sea ice on biological production and do not consider temperature and salinity changes associated with sea ice growth (Kurahashi-Nakamura et al, 2007;Sun and Matsumoto, 2010).…”
Section: Carbonmentioning
confidence: 57%
“…Recently, Kurahashi‐Nakamura et al [2007, hereafter KN2007] attempted to investigate this biological effect (sea ice blocking PAR) using an ocean‐only general circulation model. They did not explicitly model a change in sea ice coverage but simulated the effect of it by changing the sea ice mask area over which biological production is prohibited.…”
Section: Introductionmentioning
confidence: 99%
“…Our climate model has dynamical models of sea ice and ocean circulation. These features offer important advantages over both the box model of SK2000 and the ocean‐only general circulation model of KN2007, although as we note below there are some limitations to using an intermediate‐complexity model as well. In addition to the two effects of sea ice on atmospheric p CO2 (air‐sea gas exchange cap and biological production), which have been investigated previously, we also examine the effects of changes in ocean dynamics and hydrography that accompany changes in sea ice coverage in our simulation.…”
Section: Introductionmentioning
confidence: 99%